Millennial‐scale ocean acidification and late Quaternary decline of cryptic bacterial crusts in tropical reefs. Issue 5 (14th July 2014) - Riding, R.; Liang, L.; Braga, J. C.
Abstract: Ocean acidification by atmospheric carbon dioxide has increased almost continuously since the last glacial maximum (LGM), 21 000 years ago. It is expected to impair tropical reef development, but effects on reefs at the present day and in the recent past have proved difficult to evaluate. We present evidence that acidification has already significantly reduced the formation of calcified bacterial crusts in tropical reefs. Unlike major reef builders such as coralline algae and corals that more closely control their calcification, bacterial calcification is very sensitive to ambient changes in carbonate chemistry. Bacterial crusts in reef cavities have declined in thickness over the past 14 000 years with largest reduction occurring 12 000–10 000 years ago. We interpret this as an early effect of deglacial ocean acidification on reef calcification and infer that similar crusts were likely to have been thicker when seawater carbonate saturation was increased during earlier glacial intervals, and thinner during interglacials. These changes in crust thickness could have substantially affected reef development over glacial cycles, as rigid crusts significantly strengthen framework and their reduction would have increased the susceptibility of reefs to biological and physical erosion. Bacterial crust decline reveals previously unrecognized millennial‐scale acidification effects on tropical reefs. This directs attention to the role of crusts in reef formation and the ability of bioinduced calcification to reflect changes in seawater chemistry. It also provides a long‐term context for assessing anticipated anthropogenic effects.